THE VALUE OF ISLAMIC MODERATION WETU TELU IN THE CONTEXT OF ENVIRONMENTAL PRESERVATION INSIGHT - Muh. Zakaria (Universitas Islam Negeri Mataram, 2025)
This study raises the issue of the model and method of environmental preservation of Islamic Wetu Telu in Bayan, the author uses a descriptive qualitative research type with a theological approach to see the relationship between Wetu Telu beliefs and the form and method of environmental preservation. By constructing a theorySeyyed Hussein Nasr that a way to save life from the ecological crisis, namely with the firenialism model, namely humans must return to the concept of spirituality, nature must be seen as having spiritual elements. The results of the research obtained in the field that the existence of the wetu telu belief has positive implications for the preservation of the natural environment by building the concept of belief with three terms, namely mentanq, menteloq and mentioq then the three concepts also gave birth to the philosophy of nature into three, namely jagad cilik, jagad beleq (the universe).